Clinical significance of adipokine profile (leptin and adiponectin) in patients with gout - I.V. Orlova; M.A. Stanislavchuk (Bolʹ, Sustavy, Pozvonočnik, 2023)
Background. Recently, there is a lot of data on the role of leptin and adiponectin in the development and progression of rheumatic diseases. It has been studied that the increase in the level of leptin and adiponectin is associated with hyperuricemia in various pathological conditions. Data on the adipokine profile, leptin and adiponectin levels in patients with gout are limited. The purpose was to study the content of leptin and adiponectin in the serum of patients with gout depending on the course of the disease, as well as to evaluate their diagnostic value. Materials and methods. We examined 151 patients with gout (100 % men, average age 52.4 ± 9.2 years). The control group consisted of 31 practically healthy men of the same age. Results. Patients with gout had higher levels of leptin, lower levels of adiponectin and lower ratio adiponectin/leptin (lg A/L) than practically healthy men. Hyperleptinemia (leptin level > 5.91 ng/ml) was found in 49.7 % of subjects, hypoadiponectinemia (adiponectin level < 3.61 μg/ml) — in 66.9 % and dysadipokinemia (lg A/L < 3.2) — in 82.1 %. The frequency of hyperleptinemia, hypoadiponectinemia, and dysadipokinemia was significantly higher in patients with tophi in 3.9; 1.7 and 1.4 times, respectively. The phenomenon of dysadipokinemia associated with an increase in the severity of the disease — a greater number of affected joints, a greater frequency of exacerbations of gouty arthritis during the year, the severity of the pain syndrome according to the VAS, a higher level of uric acid in the blood serum (r = –0.23; r = –0.24; r = –0.35; r = –0.44; p < 0.01 for all indices). Conclusions. Patients with gout have a violation of the adipokine profile: an increase in the level of leptin, a decrease in the level of adiponectin and a decrease in their ratio (lg A/L). An increasing imbalance of adipokines is associated with a more severe course of the disease and can be considered could serve as a prognostic factor.